Association between metabolic risk, oxidative stress and psychological parameters amongst sample of nurses working in Doha, Qatar - Kirti S. Prabhu; Ummu Habeeba; Mohammad Usman Asad Rahman; Maria Salvador Perez; Salam AlMoghrabi Ramirez; Bilal Uddin Khan; Shilpa Kuttikrishnan; John Paul Ben Tabar Silang; Noora Ahmed Kh A. Al Kaabi; Abdul Quaiyoom Khan; Afsheen Raza; Mohamed Izham Mohamed Ibrahim; et al. (Clinical Epidemiology and Global Health, 2025)
Background: Shift workers are recognized to experience circadian rhythm disturbances, metabolic risks, and oxidative stress, increasing their susceptibility to numerous diseases. This study compared day and rotating shift nurses' metabolic, oxidative, and psychological profiles. Methods: A random sample of 212 eligible employees from a tertiary care hospital at Hamad Medical Corporation in Doha, Qatar, were assessed for anthropometric and laboratory parameters related to metabolic risk, oxidative stress and psychological impact. Results: Descriptive and inferential statistics (alpha = 0.05) were applied in this study. Unlike previous investigations, our study demonstrated no statistically significant correlation between changed metabolic, oxidative, and psychological profiles among nurses working day shifts compared to rotating shifts. Although abdominal obesity was slightly more prevalent among rotational workers (68.7 % vs. 63.3 %), this difference was not statistically significant (p = 0.457). Our analysis revealed that RANTES and IL9 were expressed in higher amounts amongst rotational shift duty workers. Conclusion: The study results imply that, even if not much changes were observed in metabolic and psychological differences, rotating shift workers' immunological changes might have been influenced by disruptions in their circadian rhythms. Prolonged monitoring and interventions are advised to mitigate the health hazards linked to shift work.